Effects of CaO addition into CuO/ZnO/Al2O3 catalyst on hydrogen production through water gas shift reaction - Hastuti, Zulaicha Dwi; Rosyadi, Erlan; Anindita, Hana Nabila; Masfuri, Imron; Rahmawati, Nurdiah; Rini, Tyas Puspita; Anggoro, Trisno; Prabowo, Wargiantoro; Saputro, Frendy Rian; Syafrinaldy, Ade (Center of Biomass & Renewable Energy (CBIORE), 2024)
Hydrogen is a promising renewable energy carrier and eco-friendly alternative to fossil fuels. Water-gas-shift reaction (WGSR) is commonly used to generate hydrogen from renewable biomass feedstocks. Enriching hydrogen content in synthesis gas (syngas) production can be made possible by applying the WGSR after gasification. WGSR can achieve a maximal carbon monoxide (CO) conversion using a commercially patented CZA (Cu/ZnO/Al2O3) catalyst. This study proposed three in-lab self-synthesized CZA catalysts to be evaluated and compared with the patented catalyst performance-wise. The three catalysts were prepared with co-precipitation of different Cu:Zn:Al molar ratios: CZA-431 (4:3:1), CZA-531 (5:3:1) and CZA-631 (6:3:1). The catalysts characteristics were determined through X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) analysis and Scanning Electron Microscopy (SEM) techniques. CO gas was mixed with steam in a catalytic reactor with a 3:1 molar ratio, running continuously through the catalyst at 250 °C for 30 mins. All three catalysts, however, performed below expectations, where CZA-431 had a CO conversion of 77.44%, CZA-531 48.75%, and CZA-631 71.67%. CaO, as a co-catalyst, improved the performance by stabilizing the gas composition faster. The CO conversion of each catalyst also improved: CZA-431 improved its CO conversion to 97.39%, CZA-531 to 96.71%, and CZA-631 to 95.41%. The downward trend of the CO conversion was deemed to be caused by copper content found in CZA-531 and CZA-631 but not in CZA-431, which tended to form a Cu-Zn metal complex, weakening the catalyst's activity.